Coronary endarterectomy in left anterior descending artery combined with coronary artery bypass grafting – midterm mortality and morbidity - Domaradzki, Wojciech; Sanetra, Krzysztof; Krauze, Jolanta; Kinasz, Leszek; Jankowska-Sanetra, Justyna; Świątkiewicz, Małgorzata; Paradowski, Krzysztof; Cisowski, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : Completeness of myocardial revascularization is essential in surgical treatment of coronary artery disease. The aim of this study is to determine the effectiveness of coronary endarterectomy as an adjunct to coronary artery bypass grafting (CABG) in the most difficult cases. Material and methods : Among 1559 patients who had CABG in our department, the cases of 17 who underwent an adjunct left anterior descending endarterectomy were analyzed. All procedures were performed with median sternotomy, extracorporeal circulation and in mild hypothermia (34 o C), by the same surgeon. No coronary artery endarterectomy was planned before surgery. Results : There was no infarction or cardiac arrest during hospitalization. Only one patient required mechanical circulatory support (intra-aortic balloon counterpulsation). Each patient was contacted and investigation for major adverse cardiac and cerebrovascular events (MACCE) was performed. Eleven patients (65%) already underwent midterm clinical evaluation. There was no death, myocardial infarction or cerebrovascular incident during the entire period (mean follow-up at 15.3 months). One patient required urgent coronarography due to chest pain. No other patient had chest pain or significant deterioration of ventricular function in echocardiography. Conclusions : Outcomes and potential indications for performing left anterior descending coronary endarterectomy as an adjunct to CABG are discussed.